O design gráfico retrô no projeto de cartazes art déco para o theatro São Pedro - Gomes, Rafael Peduzzi (Universidade do Vale do Rio dos Sinos, 2015)
In this paper we aim to project a sequence of posters from events of the Theatro São Pedro schedule, using retro design graphic as tool. We use the art deco style as main theme from the retro concept, bringing its application to our project. During the development of the research, we studied the history of Theatro São Pedro and its relevance to the local community. We define our approach to graphic design as focused in its symbolical aspects and its expressive potential. Our choice for the poster is sustained as an historical rescue in the actuality. We also expose the retro’s meaning during the history, mentioning its concept since the 60’s until today, which it is currently seen as an advertising tendence. And we build an historical scheme of art deco to develop its consolidation as a style, featuring aspects to present in our project, as the aerodynamic, modern and decorative geometry. We introduce the choices for the practical Project and the methodological orientation, which were based in the methods of Munari (2008) and the techniques of moodboard (PEREIRA; SCALETSKY, 2011). We discuss the final results, explaining the relations of our practice with the research, concluding that the retro can be used nowadays as a design tool and as a stylistic resource, becoming a commercial reasoning for brands and products.
Keywords: Design gráfico; Retrô; Cartaz; Art déco; Graphic design; Poster